KRITIK UNTUK KRITIK TARIÃ¢â‚¬ MINAT YANG TERJAUHI OLEH PENGGIAT TARI - Eko Supriyanto (Gelar : Jurnal Seni Budaya, 2010)
Dance critic in the performing arts becoming a rare field, which people in performing arts are more concern on keen observers and practitioners. In the dance world, the Republic of Dance open many possibilities including the field of dance critic to delivered the ideality to critic of dances. Thus, it should be more established on writing not only as reviews, description, nor personal experiences; but also, the depth of intuition, sense of aesthetic, expertise on the field of performing arts, evaluation, and technique of choreography, dance, music and state production. This field of study is open many opportunities for dancer and choreographer to challenge the continuity and life of the dance world in Indonesian performing arts. Key words : dance, critic, performing art